Public infrastructure and housing prices: An application of geographically weighted regression within the context of hedonic prices (2020)
The analysis of externalities in real state has been matter of study during the past few years. In this paper we use both conventional and spatial econometric model, as well as geographically weighted regression models, to measure the effect of the San Javier Metro Station (in Medellín, Colombia) on the housing prices of the surrounding area. The main finding of this study is that the metro station has a positive impact on the prices of houses located within a radius of 600 meter from the station. However, the railroad track accessing the station has a negative impact on housing prices located nearby.